The Behavioral and Immunological Impact of Maternal Separation: A Matter of Timing - Roque, Susana; Mesquita, Ana Raquel; Palha, Joana A.; Sousa, Nuno; Correia-Neves, Margarida (Frontiers in Behavioral Neuroscience, 2014)
Maternal separation (MS), an early life stressful event, has been demonstrated to trigger neuropsychiatric disorders later in life, in particular depression. Experiments using rodents subjected to MS protocols have been very informative for the establishment of this association. However, the mechanism by which MS leads to neuropsychiatric disorders is far from being understood. This is probably associated with the multifactorial nature of depression but also with the fact that different research MS protocols have been used (that vary on temporal windows and time of exposure to MS). In the present study MS was induced in rats in two developmental periods: for 6 h per day for 14 days between postnatal days 2-15 (MS2-15) and 7-20 (MS7-20). These two periods, were defined to differ essentially on the almost complete (MS2-15) or partial (MS7-20) overlap with the stress hypo-responsive period. Behavioral, immunological and endocrine parameters, frequently associated with depressive-like behavior, were analyzed in adulthood. Irrespectively from the temporal window, both MS exposure periods led to increased sera corticosterone levels. However, only MS2-15 animals displayed depressive and anxious-like behaviors. Moreover, MS2-15 was also the only group presenting alterations in the immune system, displaying decreased percentage of CD8+ T cells, increased spleen T cell CD4/CD8 ratio, and thymocytes with increased resistance to dexamethasone-induced cell death. A linear regression model performed to predict depressive-like behavior showed that both corticosterone levels and T cell CD4/CD8 ratio explained 37% of the variance observed in depressive-like behavior. Overall, these findings highlight the existence of “critical periods” for early life stressful events to exert programming effects on both central and peripheral systems, which are of relevance for distinct patterns of susceptibility to emotional disorders later in life.